Survival with chronic myeloid leukaemia after failing milestones - Lauseker, Michael; Hehlmann, Rüdiger; Hochhaus, Andreas; Saußele, Susanne (Leukemia, 2023)
Therapy after failing response milestones in CML is controversial. Risks associated with comorbidities, drug toxicities or transplantation may preclude switching to another tyrosine kinase inhibitor (TKI) or other treatments. No information on long-term survival of failing patients is available. To systematically analyse survival after reaching, or not reaching, response milestones, 1342 patients from CML-study IV with newly diagnosed CML in chronic phase and regular molecular tests were studied. Landmark survival analyses were done by <0.1%, 0.1-1%, >1-10% and >10% BCR::ABL1IS at 3, 6, 12 and 24 months up to 14 years. 10- to 12-year survival of patients who failed the failure milestones (>10% BCR::ABL1IS at 6 months, >1% BCR::ABL1IS at 12 months) ranged around 80%, 10% less than in responding patients. These results suggest revision of milestones. Age (more or less than 60 years) had no major impact on survival differences, but on hazard ratios and CML-specific survival. Switching to alternative therapies, which was observed in 26.9% of the patients, did not change the main results. The data show that TKI-treated patients not reaching failure milestones still may derive benefit from continuing TKI-treatment and provide a basis for individualised decisions, if failing patients are confronted with risks of alternative treatments.